Organizational Commitment and Job Satisfaction as the Basis of Organization Buildingtional Citizenship Behaviour (OCB) and the Implications on Employee Performance - I Ketut Setia Sapta; Nengah Landra; Ni Made Satya Utami; I Made Purba Astakoni (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this research is to analyze the influence of organizational commitment and job satisfaction as the basis for building Organizational Citizenship Behavior (OCB), and analyzing the effect of OCB employees on the performance of employees of the Notary Office in Bangli Regency. The population and research sample were collected through online surveys from 14 Notary Offices in Bangli Regency and appointed 45 employees as respondents. The data analysis technique used the Partial Least Square (PLS) approach. PLS is a component or variant based on Structural Equation Modeling (SEM) equation models.BB based on the hypothesis testing that has been done, it can be concluded: (1) Job satisfaction has a positive and significant effect on OCB, meaning that this indicates that the higher the level of employee job satisfaction, the employee's OCB will also increase; (2) Organizational commitment has a positive and insignificant effect on OCB. OCB has a positive and significant effect on employee performance, this shows that the higher the employee's OCB level, the higher the employee's performance at the Notary Office in Bangli Regency